Cooper Curtice papers - Curtice, Cooper, 1856-1939.
Correspondence, diary, writings, speeches, notes, Curtice (Curtis) family papers, biographical and genealogical material, scrapbook, clippings, printed matter, and other papers relating chiefly to Curtice's research into animal diseases. Topics include babesiosis in cattle, also known as Texas fever; eradication of its carrier, the cattle tick; and diseases in sheep and turkeys. Correspondents include Alpheus Hyatt, Veranus A. Moore, Theobald Smith, and Charles D. Walcott.
Library of Congress Prints and Photographs Division.
Agriculturist and parasitologist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hyatt, Alpheus, -- 1838-1902 -- Correspondence; Moore, Veranus A. -- 1859-1931 -- Correspondence; Smith, Theobald, -- 1859-1934 -- Correspondence; Walcott, Charles D. -- 1850-1927 -- Correspondence; Curtis family; Animals -- Diseases; Babesiosis in cattle; Cattle -- Diseases; Sheep -- Diseases; Ticks as carriers of disease; Turkeys -- Diseases; Agriculturists; Parasitologists